Grafted tomato (Solanum lycopersicum) varieties on wild brinjal (Solanum melongena) rootstocks for growth, yield, fruit quality and economics - VERMA, LALIT KUMAR; BAHADUR, VIJAY; KERKETTA, ANITA; TOPNO, SAMIR E; MAYANK; DIXIT, AMIT (The Indian Journal of Agricultural Sciences, 2025)
Grafting is a horticultural technique that involves joining tissues from one plant (scion) with another (rootstock) to create a new plant. Grafting allows the combination of desirable traits from different plants. Therefore, the present study was conducted during the rainy (kharif) season of 2022–23 and 2023–24 at Naini Agricultural Institute, Sam Higginbottom University of Agriculture, Technology and Sciences, Prayagraj, Uttar Pradesh to investigate the effects of tomato grafting on wild brinjal rootstocks on tomato yield, quality, and economics of tomato production. The experimental design employed was a randomized block design (RBD). Treatment T1 (S. torvum + Kashi Anupam) performed best for maximum percentage of grafting success (73.83%). The growth parameters recorded include plant height, which measured 39.97 cm at 30 days after transplanting (DAT) and 79.05 cm at 60 DAT, and the number of branches/plant, which averaged 16.80. The minimum number of days to first flowering was observed in treatment T2 (Solanum torvum + Kashi Sharad), with an average of 58.16 days. Yield parameters revealed an average fruit weight of 76.13 g and a yield of 70.40 t/ha. Nutritional quality analysis showed a Vitamin C content of 21.54 mg/100 g and a lycopene content of 11.57 mg/100 g. The economic evaluation resulted in a benefit-cost (B:C) ratio of 3.85, indicating high profitability.